Investigation on hydrogen-fueled combustion characteristics and thermal performance in a micro heat-recirculation combustor inserted with block. (22nd October 2021) - Wei, Jia; Fu, Guang; Yang, Wenming; Li, Shaobo; E, Jiaqiang; Peng, Qingguo; Zhang, Ansi
Abstract: Numerical investigation on the premixed H2 /air combustion in a micro heat-recirculation combustor inserted with/without block is conducted. Effects of block setting, heat-recirculation, and flow rate on combustion characteristics and thermal performance are depicted and analyzed. The results demonstrate that the block enhances the flame stability and preheating effect, which also reduces the heat loss via exhaust gas, while it shortens reactants residence time. The combustor setting with a transverse block gains a better thermal performance than that inserted with a longitudinal block. With the increase of transverse block height, the high-temperature zone is broadened and radiation is improved. However, the block with a height of 10 mm separates the fluid field and weakens the effects of heat recirculation, leading to a lower outer wall temperature. Furthermore, the appropriate block insertion method and height contribute to the significant improvement of heat transfer, radiant efficiency and further optimization of micro power generator. Highlights: Premixed H2 /air combustion in a micro combustor with block is investigated. Effects of block on combustion characteristic and heat transfer are analyzed. Reactants preheating and heat transfer are enhanced by the inserted block. Optimized block form and height are achieved for better thermal performance.